Mechanical and thermal properties of graphene nanomeshes - Mostério, Newton Cunningham Braga; Fonseca, Alexandre F. [UNESP] (Springer Nature, 2013)
Graphene possesses excellent mechanical, thermal and electronic properties, not to mention its optical transparency and chemical stability. Much effort has been made towards the control of its physical properties for technological applications. One way to achieve this control is by modifying graphene size and structure. Recently, in a search for the development of semiconducting graphene structures to be produced at large scale, a new structure called graphene nanomesh was synthesized by means of block copolymer lithography and other methods. Basically, a graphene nanomesh is a graphene structure made to possess a periodic array of nanoscale holes whose sizes and hole-to-hole (or neck) distances are considered as control parameters for its overall electronic properties. Although the electronic properties of graphene nanomeshes are being intensively studied, their mechanical properties are still to be investigated. This work, then, presents the first study of mechanical, structural and thermal properties of graphene nanomeshes as a function of hole and neck sizes, through atomistic molecular dynamics simulations. The dependence of the Young's modulus and coefficient of thermal expansion of graphene nanomeshes on the hole and neck sizes will be shown. © 2013 Materials Research Society.